2016
DOI: 10.4103/2321-0656.176579
|View full text |Cite
|
Sign up to set email alerts
|

A study on the quality of life of patients with type 2 diabetes mellitus and hypertension presenting to a tertiary care hospital in Southern India

Abstract: 3. Cullen KW, Buzek BB. Knowledge about type 2 diabetes risk and prevention of African-American and Hispanic adults and adolescents with family history of type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…The WHOQOL-BREF (10 studies)[ 25 26 29 30 35 36 57 58 59 60 ] and SF 36 (eight studies)[ 15 23 31 32 41 45 47 56 ] are the most commonly used generic instruments among T2D subjects in India. One study used both generic and diabetes-specific tools for QoL assessment and found that both instruments are equally effective and reliable in the evaluation of QoL among diabetes patients.…”
Section: R Esultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The WHOQOL-BREF (10 studies)[ 25 26 29 30 35 36 57 58 59 60 ] and SF 36 (eight studies)[ 15 23 31 32 41 45 47 56 ] are the most commonly used generic instruments among T2D subjects in India. One study used both generic and diabetes-specific tools for QoL assessment and found that both instruments are equally effective and reliable in the evaluation of QoL among diabetes patients.…”
Section: R Esultsmentioning
confidence: 99%
“… n =150 Sample size justification: not provided Study period: June 2016 to May 2017 28 GDM (cases) and 118 GDM negative (controls) Mean age of cases=24.82 ± (3.9) Mean age of controls=23.31 ± (3.9) SF-36 V2 Physical Component Score=42.6 ± (18) cases and 55.2 ± (19.1) (control) Mental Component Score=50 ± (14.7) cases and 62.2 ± (14.9) (control) Factors associated with QoL-Women with higher socioeconomic class had better QoL as compared to lower socioeconomic class. [ 59 ] Gosain V et al ., 2016 Mandya Karnataka South India Cross-sectional. Tertiary care hospital.…”
Section: Appendixmentioning
confidence: 99%